COMPARATIVE STUDY OF THE PANCREAS HISTOLOGICAL AND HISTOCHEMICAL IN BARN OWL (TYTO ALBA) AND BLACK FRANCOLIN (FRANCOLINUS) - Eyhab R. Al-samawy; Mustafa Salah Hasan; Hawraa Faisal Mishal (Journal of Medical Genetics and Clinical Biology, 2024)
The present study aimed at the pancreas of two bird species differs in their classification, habitat, nutrition, and activity. The birds were omnivorous Black Francolin(francolinus) and carnivorous Barn Owl (Tyto alba). Histologically the pancreas of these birds was covered by a thin layer of connective tissue capsule formed from reticular, elastic, and few collagenous fibers, this capsule in barn owl appear thicker than that found in black francolin birds. The parenchyma of pancreas in both birds were composed mainly from exocrine portion represented by serous acini and endocrine portion which distributed among acini which represented by islets of Langerhans. The endocrine gland of the pancreas showed that the islets of Langerhans, have two types of cells, the first one is alpha cells shown as a spindle in shape with oval nuclei, located periphery of the islets of Langerhans. The second type was beta cells show as rows or irregular polygonal cells with spherical nuclei that is slightly larger than the nuclei of alpha cells and found in the center of islets. These cells were located in the periphery of the island of Langerhans in both birds. Histochemical results reveal that the pancreatic cells, whether the acinar cells or islets cells are moderately positive in both species of birds.